Self-Concept Enhancement through Group Guidance with Sociodrama Techniques for Class X MIPA 1 Students of SMA Sauqi Nusantara - Heni Kartikasari; Hardi Prasetiawan (Budapest International Research and Critics University, 2022)
This study aimed to improve the self-concept of students in Class X MIPA 1 (Natural Science I tenth class) of SMA Sauqi Nusantara (Sauqi Nusantara Senior High School) by applying sociodrama techniques in group counseling. This research was a classroom action research (CAR) conducted in two cycles, where each cycle consisted of action planning, action implementation, observation, and reflection. The research subjects were students in Class X MIPA 1, SMA Sauqi Nusantara, totaling 29 people. Sources of data originated from teachers, students, and the learning process. The data collection was performed by observation, interviews, documentation, and questionnaires. The data validity test employed triangulation techniques, while data analysis used a comparative descriptive analysis technique. The results revealed that counseling service activities could be categorized as running very well both on teacher activities and student activities in the classroom so that the counseling service process runs appropriately. The achievement of pre-cycle counseling service activities was 74.42%, rising to 75.73% in the first cycle (Cycle I), and in the second cycle (Cycle II), it improved to 84.09%. The application of the sociodrama techniques in group counseling could enhance the self-concept of students in Class X MIPA 1 of SMA Sauqi Nusantara from pre-cycle to Cycle I and from Cycle I to Cycle II. The achievement of the self-concept of students at pre-cycle was 66%, increasing to 73% in Cycle I, and in Cycle II, it improved to 77%. Based on the research and discussion results, it can be concluded that the sociodrama techniques in group counseling service could enhance the self-concept of students in class X MIPA 1 of SMA Sauqi Nusantara.